INDIVIDUAL FACTORS CONTRIBUTING TO UTILIZATION OF DIABETIC MEDICATIONS AMONG PATIENTS AGED 45 YEARS ATTENDING THE DM CLINIC AT MPIGI HCIV IN MPIGI DISTRICT. A CROSS-SECTIONAL STUDY - MATOVU, PRECIOUS BRONIA N.; Okwany, Jimmy; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2024)
Background Diabetes is a chronic metabolic disorder characterized by elevated blood sugar levels due to the body’s inability to produce or effectively utilize insulin. The study aims to assess the individual factors contributing to the utilization of Diabetic medications among patients aged 45 years attending the Diabetic clinic at Mpigi District. Methodology The study employed a cross-sectional observational study design. Simple random sampling was used to select participants the study involved simple random sampling. A sampling frame was prepared, consisting of eligible patients attending the diabetic clinic at Mpigi HCIV. Quantitative data was analyzed using appropriate statistical techniques such as descriptive statistics like frequencies, percentages, means, and standard deviations, which were calculated to describe Results Most 33 (66%) participants were above the age of 50, Most 29 (58%) participants reported taking antidiabetic medication for below 1 year, 39(78%) individuals reported currently taking medication, 23 participants demonstrated good drug adherence (6-8), accounting for 46%, 23 participants stated they understood well, comprising 46%, 37(74%) participants could specify and name the medications they were currently taking. 27 (54%) participants were very confident in their management regimen. 35(70%) individuals reported no concerns affecting their drug uptake. 32(64%). participants stated they had not experienced any side effects, making up 64%. Conclusion Individual factors influencing medication utilization among individuals with diabetes in Uganda were Age, education, income, and social support are critical determinants of adherence to diabetic medications. Gender, cultural beliefs, and health literacy also play significant roles in medication utilization. Recommendations Patient Education Implement comprehensive patient education programs to improve health literacy, enhance understanding of diabetes, and increase awareness of the importance of medication adherence to address that 46% of participants had a good understanding of the purpose and benefits of their medication.